1996
DOI: 10.1074/jbc.271.10.5884
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of the Full-length cDNA of (S)-Hydroxynitrile Lyase from Hevea brasiliensis

Abstract: The full-length cDNA of (S)-hydroxynitrile lyase (Hnl) from leaves of Hevea brasiliensis (tropical rubber tree) was cloned by an immunoscreening and sequenced. Hnl from H. brasiliensis is involved in the biodegradation of cyanogenic glycosides and also catalyzes the stereospecific synthesis of aliphatic, aromatic, and heterocyclic cyanohydrins, which are important as precursors for pharmaceutical compounds. The open reading frame identified in a 1.1-kilobase cDNA fragment codes for a protein of 257 amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
98
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 33 publications
3
98
1
Order By: Relevance
“…The amino acid sequences of ACC1 of yeast (21), rat (22), chicken (23), and human (12) are very similar, with Ϸ90% identity among the animal ACC1 carboxylases and Ϸ35% similarity between the animal and yeast ACC1 enzymes. In the yeast, Saccharomyces cerevisiae, acetyl-CoA carboxylase (ACC1͞FAS3), the ACC homolog of animal ACC1, is essential for the growth and viability of the yeast cells, and supplementation of fatty acids failed to rescue the acc1 null mutants (24,25).To dissect the roles of the two animal ACC isoforms, we perused knockouts of the ACC1 and ACC2 genes in mice. Our studies with Acc2 knockout mice have shown that Acc2 Ϫ/Ϫ mice live and breed well, continuously oxidize fatty acids, eat more food, and gain less weight than their wild-type cohorts (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acid sequences of ACC1 of yeast (21), rat (22), chicken (23), and human (12) are very similar, with Ϸ90% identity among the animal ACC1 carboxylases and Ϸ35% similarity between the animal and yeast ACC1 enzymes. In the yeast, Saccharomyces cerevisiae, acetyl-CoA carboxylase (ACC1͞FAS3), the ACC homolog of animal ACC1, is essential for the growth and viability of the yeast cells, and supplementation of fatty acids failed to rescue the acc1 null mutants (24,25).To dissect the roles of the two animal ACC isoforms, we perused knockouts of the ACC1 and ACC2 genes in mice. Our studies with Acc2 knockout mice have shown that Acc2 Ϫ/Ϫ mice live and breed well, continuously oxidize fatty acids, eat more food, and gain less weight than their wild-type cohorts (4).…”
mentioning
confidence: 99%
“…The amino acid sequences of ACC1 of yeast (21), rat (22), chicken (23), and human (12) are very similar, with Ϸ90% identity among the animal ACC1 carboxylases and Ϸ35% similarity between the animal and yeast ACC1 enzymes. In the yeast, Saccharomyces cerevisiae, acetyl-CoA carboxylase (ACC1͞FAS3), the ACC homolog of animal ACC1, is essential for the growth and viability of the yeast cells, and supplementation of fatty acids failed to rescue the acc1 null mutants (24,25).…”
mentioning
confidence: 99%
“…In yeast, cytoplasmic ACC is a single trifunctional polypeptide of 2233 amino acids and with an approximate molecular mass of 250 kDa (10 -12). The ACC-encoding gene has been isolated and was designated as ACC1 and FAS3, respectively (11,12). Unlike fatty-acid synthase mutants, which grow upon fatty acid supplementation, ACC1 disruption is lethal and cannot be compensated by external long-chain fatty acids (12,13).…”
mentioning
confidence: 99%
“…The ACC-encoding gene has been isolated and was designated as ACC1 and FAS3, respectively (11,12). Unlike fatty-acid synthase mutants, which grow upon fatty acid supplementation, ACC1 disruption is lethal and cannot be compensated by external long-chain fatty acids (12,13). This characteristic is commonly attributed to the malonyl-CoA requirement of cellular very long-chain fatty acid biosynthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation